Prevalence of Denture Stomatitis Among Complete Denture Patients - A Retrospective Study - SUNIL, NURUL SYAMIMI BINTI MOHD AZLAN; M.D.S., REVATHI DURAISAMY (The journal of contemporary issues in business and government, 2021)
Denture stomatitis is a common oral mucosal lesion occurring in mucosa underneath a denture. It is characterised by mild inflammation and erythema of oral mucosa covered by denture. Denture stomatitis have a negative impact on the general health and overall well-being of patients. Therefore, there is a need to understand the pattern of prevalence in age and gender in hopes to provide treatment for such lesions and prevent recurrence. The aim of this study was to evaluate the prevalence of denture stomatitis among complete denture patients. The study includes adults, both males and females, who reported to Saveetha Dental College between June 2019 to March 2020. Inclusion criteria includes complete denture wearers. Patients below 18 years of age were excluded from the study. Among total data of 86000 patient records, 80 patient records were analysed and retrieved with the parameters such as patient’s age, patient’s gender and presence of denture stomatitis were collected. Datas were recorded in Microsoft Office Excel (2013) and analysed using SPSS software Version 26.0 and chi-square test was done to find out correlation between variables such as age group and gender. Significance test level was set at p<0.05. A total of 80 patients presented with existing complete dentures, which includes 44 females and 36 males. 13.8% were 21-40 years, 38.8% were 41-60 years and 47.5% were 61-80 years age group. 67.5% of patients presented with denture stomatitis. The highest prevalence of denture stomatitis was found in the age group 41-60 years (83.9%), followed by 21-40 years (81.8%) and 61-80 years (50%). Statistically significant difference was observed between age groups and denture stomatitis (p<0.05). Denture stomatitis was found in 70.5% of females and 63.9% of males but no significant difference was found between genders (p>0.05). Within the limits of this study, it was observed that there was high prevalence of denture stomatitis in complete denture patients with the age group between 41 to 60 years age group and in female patients.